O narrador e as personagens femininas em Badu (1932), de Arnaldo Tabayá - Bosco, Bianca (Universidade Federal de São Carlos, 2020)
The following dissertation wants to rescue the literary work called Badu (1932), written by the Brazilian author Arnaldo Tabayá (1901-1937). Being this one the only novel released by the writer, it received a lot of recognition from the critics by the time of its release, although many positive critics were not enough to stop that both the author and the book were forgotten in the following years. It is made, roughly, a general panorama from the tales and poems that Tabayá writes in newspapers, before and after the novel’s publication, so the reader can be familiar with his literary production. Also, it is important to consider the criticism and review the book received by that time. The truth is that, until today, not many deep analyses were made from Badu (1932), especially considering the historical and literary context in which Brazil found itself. Knowing that, it is necessary to revisit and relate the social aspects and the characteristics from the 1930’s Brazilian Novel, when many important books were launched. This literary movement is known for prioritize, by literature, the representation from the reality of the country, not hiding its imperfections and exploring aspects that were not problematized by then. Badu (1932) is important that way, because, by being part of this movement, it draws attention to problems from Rio de Janeiro’s society, where the novel happens. The image middle class men had from women is one of the main points explored in Tabayá’s narrative, in which the narrator represents the masculine view over the feminine universe. Using Luís Bueno’s (2015) terms, the reducing roles imposed to women were the prostitute and the wife, no half term – and restlessness caused by the nonconformity it was not exclusivity from Badu (1932), but from many 1930’s novels. The study object still has many female characters that show a lot more depth and meaning that the narrator can show and see, and not only the ones he relates romantically, but also his relates and acquaintances. Even with the big gap between the book’s release and current days, many of the criticism made by the author are very relevant nowadays and can be used to comprehend 1930’s society a little bit more, fact that shows its importance and then it fits as a member from the 1930’s Brazilian novel.
The narrator and female characters in Badu (1932), by Arnaldo Tabayá
Keywords: Arnaldo Tabayá; Romance de 1930; Badu; Personagens femininas; Literatura brasileira; 1930's brazilian novel; Female characters; Brazilian literature; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA BRASILEIRA